Integrated Sociology Program Assessment: Inclusion of a Senior Portfolio Graduation Requirement. - Crockett, Jason; Hu, Albert; Greenwood, Joleen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2018)
This article presents information about the planning, implementation, and findings of an assessmentbased student portfolio designed by the faculty of a sociology program at Kutztown University of Pennsylvania, a midsized public regional liberal arts institution. First, we briefly present the rationale for implementing a portfolio system and the thought process by which our particular portfolio assessment tool was created. Then, we explain our findings using the portfolio assessment system and how these findings were used to modify and strengthen the program as well as serve as a basis for long-term planning for the program.